Violence against Male in Abu Ghraib in The New Yorker's political Reports: A Critical Study - Sameer, Mustafa Mohammed Rasheed; Sameer, Emad Hayif (Al-Adab Journal, 2023)
The present study under the title " Violence against Male in Abu Ghraib in The New Yorker's political Reports" is interested in revealing issues of power, dominance and ideologies in the political reports which talk about violence against men in Abu Ghraib. Revealing these issues in the report will be according to the use of CDA approach depending on the two scholars who are interested in this approach, Tuen Van Dijk, Norman Fairclough. In this study, there is a use of language as a tool to express the dominance, power and ideology. With these linguistic elements, the previous issues are exploited indirectly by the American forces. We aim in this study to identify all the linguistic elements which symbolize violence in the selected report. Then, we will explain its function in this report which is used pragmatically. After that, we explain the issues of power, dominance and ideologies and check whether they are used in these reports implicitly or explicitly. We selected one report to be analysed in this paper. This report was taken from the American weekly magazine "The New Yorker". Selecting these Extracts was based on the using of many linguistic elements which refer to violence in Abu Ghraib. We used the qualitative approach in analyzing the data, because we deal with behavioral study, and it is the preferable approach in analyzing studies like these. In this method, we depend on the narrative way in the analysis rather than using numbers or statistics. The model adopted in this study will be eclectic one depending on Fairclough's three-dimensional approach and Van Dijk's socio-cognitive approach. These models are interested in the texts with their social and cultural function. The findings have included the use of linguistic elements of violence in these reports in many lines. The function of these linguistic elements was used indirectly in a hidden way. The study also revealed that issues of power, dominance and ideologies were exploited pragmatically in the American speeches. Our aims and Hypothesis have been achieved in the findings and conclusions. In the last lines of chapter five, we gave some recommendations and suggestions for further studies.